Static test compaction for circuits with multiple independent scan chains. Issue 1 (1st January 2016) - Pomeranz, Irith
Abstract : This study describes a static test compaction procedure for transition faults in circuits with multiple scan chains where each scan chain can operate independently in functional or shift mode. The procedure mixes parts of different broadside and skewed‐load tests, where the parts coincide with the scan chains, in order to create new tests that detect more faults. This allows the number of tests to be reduced without reducing the fault coverage. By mixing parts of tests with different types, different scan chains are assigned different modes of operation within the same test. Experimental results are presented to demonstrate that this allows the number of tests to be reduced below the number of tests in a compact test set that consists of broadside and skewed‐load tests.